Implementation of Marketing Mix to Increase Meeting Events - Kadek Wirantari; I Nyoman Rajin Aryana; I Ketut Sutama; I Gede Mudana; Made Ruki; I Gusti Agung Bagus Mataram (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: This study aims to analyze the application of marketing mix in this case 7Ps (product, price, place, promotion, people, process, and physical evidence) in increasing the number of meetings at a 5-star hotel located in Kuta area, Bali, Indonesia. Research methods: Data collection was carried out by observation, interviews, documentation, and questionnaires with a total of 150 respondents from professional conference organizers who had held a meeting at the hotel. The analysis technique used in this study is qualitative and quantitative analysis. Results and discussion: The implementation of the marketing mix applied by the hotel is such as providing a meeting place including facilities and meeting equipment, providing prices following client budgets, promoting using brochures, websites, through sales calls and telemarketing, routinely checking the conditions of the meeting place. The most effective variable influencing the increase in the number of meeting events is by looking at the results of the beta standard coefficient of the largest value, namely the physical evidence variable with the largest value of 0.266 with sig 0.00 which means that the physical evidence variable most effectively influences the number of meetings Implication: The factors causing the ineffectiveness of the variable of the marketing mix based on the results of the interview are less than optimal employee performance and promotions that are carried out less and are less effective in selling meeting packages. Keywords: marketing mix, meeting events, multiple linear analysis regression.